A core undergraduate curriculum in plastic surgery – a Delphi consensus study in Scandinavia. Issue 2 (4th March 2018) - Almeland, Stian K.; Lindford, Andrew; Berg, Jais Oliver; Hansson, Emma
Abstract: Background and aims: In recent years, undergraduate medical education has undergone a transition from a speciality-based to a more competence-based training system. Consequently, whilst medical knowledge is rapidly expanding, time for teaching of the surgical specialties is decreasing. Thus, there appears to be a need to define the core competences that are to be taught. The aim of this study was to establish a Scandinavian core undergraduate curriculum of competences in plastic surgery, using scientific methods. Methods: The Delphi technique for group consensus was employed. An expert panel was recruited from various plastic surgery subspecialties, institutions, and levels of clinical experience, in four Nordic countries (Denmark, Finland, Norway and Sweden). Questionnaires were sent out and answers collected electronically via Google Forms™. Following completion of three predefined rounds of anonymous questionnaires; a final core curriculum competency list was agreed upon based on a consensus agreement level of 80%. Results: Two hundred and ninety-five competences were suggested in the first round. In the second round, 76 competences (33 skills and 43 knowledge items) received a score ≥3.00 on a 1–4 Likert scale. Final agreement in the third round resulted in a list of 68 competences with agreement above 80% (31 skills and 37 knowledge items). Conclusions: This study proposes the first scientifically developed undergraduate core curriculum in plastic surgery. It comprises of a consensus of competences a recently graduated medical doctor should be expected to possess.